AVALIAÇÃO CEFALOMÉTRICA DA ESTABILIDADE DO TRATAMENTO COM O REGULADOR DE FUNÇÃO FRÄNKEL-2 - Andreoli, Flávio Augusto Meffe (2008)
The aim of this study consisted of comparing dental, skeletal and soft tissue effects promoted by Frankel-2 functional regulator with a control group, besides observing the stability of those effects, in an average post-treatment period of 7.11 years. The sample had a total of 90 lateral cephalometric radiographs, with 54 cephalometric radiographs of 18 FR-2 treated patients assessed in three phases (T1: treatment beginning; T2: treatment ending and T3: post-treatment) and 36 cephalometric radiographs of 18 control patients observed in two time periods (T1 and T2). To compare control and treated groups a Student non-paired t-test was used. The comparison of the treated group values in the three times (T1, T2, and T3) was done by the one criterion Analysis of Variance (ANOVA) and Tukey test (p<0.05). The main changes provided by the FR-2, observed, by means of comparison with treated and control groups, involved mandibular effects: mostly protrusion and mandibular length increase associated with clockwise rotation of the mandible, which resulted in an increased total (N-Me) and lower (AFAI) facial height, besides a soft counterclockwise rotation of the palatine plane (SN.PP). The maxillary incisors retracted and the mandibular incisors tipped to buccal side. There was a relative distalization of the maxillary molars in conjunction with the overjet decrease, so, the convexity of the soft tissue facial profile was better. In post-treatment period, it was observed a sagittal stability of maxilla SNA) and mandible (SNB), of the facial pattern variables, of the maxillary incisor inclination, of the nasolabial angle and of the overjet. The maxilla and the mandible continued to grow in the anterior-posterior direction, together with the facial heights. There were also the incisors and molars extrusion. Already, the oclusal plane and the gonium angle decreased in this phase.(AU)